THE EFFECT OF EXCHANGE RATES, INFLATION, JCI AND THE NUMBER OF ISLAMIC MUTUAL FUNDS ON THE NET ASSET VALUE OF ISLAMIC MUTUAL FUNDS (NABRS) IN INDONESIA - Dini Setyani; Tri Gunarsih (Journal of Applied Economics in Developing Countries, 2018)
This study aims to analyze the effect of exchange rates, inflation, JCI and the number of Islamic mutual funds on the Net Asset Value of Islamic Mutual Funds (NABRS) in Indonesia. Net Asset Value is one indicator of the results of the mutual fund portfolio. The data used is monthly time series data from January 2010 to February 2018. The data source for NABRS is from the publication of the Financial Services Authority (OJK). The results of the regression analysis show that the exchange rate, inflation, JCI and the number of Islamic mutual funds have a significant influence on NABRS. Exchange rates have a negative effect, inflation has a positive influence, JCI has a positive influence and the number of Islamic mutual funds has a positive influence on NABRS. This shows that the exchange rate, inflation, JCI and the number of Islamic mutual funds can be used as consideration by investors in investing in Islamic mutual funds.Keywords:  Exchange Rate, Inflation, JCI, Number of Islamic Mutual Funds, Islamic Mutual Fund NABs